1999
DOI: 10.1063/1.370806
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Cd in GaAs and its correlation with self-diffusion on the Ga sublattice

Abstract: Cd diffusion into GaAs single crystals has been investigated in the temperature range 756–1201 °C. Penetration profiles measured by secondary ion mass spectroscopy and spreading-resistance profiling agree with each other and are numerically reproduced on the basis of the kick-out diffusion mechanism. A major involvement of vacancies via the dissociative mechanism can be excluded. This enables us to deduce from the Cd profiles effective Cd diffusivities (Dseff) as well as Ga diffusivities (DISD) mediated by dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…Earlier experiments that indicated that the more highly positively charged states (+2 and +3) of gallium interstitials are the most important charge states for diffusion, on the other hand, were prepared with more significant concentrations of p-type dopants. 2,6,7,67 Our calculations support this conclusion as well, because this material was prepared under the more heavily p-doped conditions which favor gallium interstitial diffusion in the +2 or +3 charge states. The authors of one of these papers noted that there were difficulties involved in using +2 charged gallium interstitials to properly fit the diffusion profiles in the regions with low concentrations of dopants, and that the solution to these difficulties would probably involve the use of +1 charged interstitials in the model, in addition to +2 and +3 charged interstitials.…”
Section: Fig 19 (Color Online)supporting
confidence: 67%
See 3 more Smart Citations
“…Earlier experiments that indicated that the more highly positively charged states (+2 and +3) of gallium interstitials are the most important charge states for diffusion, on the other hand, were prepared with more significant concentrations of p-type dopants. 2,6,7,67 Our calculations support this conclusion as well, because this material was prepared under the more heavily p-doped conditions which favor gallium interstitial diffusion in the +2 or +3 charge states. The authors of one of these papers noted that there were difficulties involved in using +2 charged gallium interstitials to properly fit the diffusion profiles in the regions with low concentrations of dopants, and that the solution to these difficulties would probably involve the use of +1 charged interstitials in the model, in addition to +2 and +3 charged interstitials.…”
Section: Fig 19 (Color Online)supporting
confidence: 67%
“…The authors in Refs. 3 and 8 conclude from their own measurements and from re-analysis of the results of Bösker 6,7 that interstitial gallium in the neutral and singly positive charge states are partial contributors to gallium diffusion, with gallium vacancies contributing more strongly over much of the experimentally accessible range of stoichometry and doping level. Under arsenic-rich conditions, these authors observe an enhanced contribution of gallium vacancies to gallium diffusion.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…4 -6͒, Ge, 7 and to a lesser extent in GaAs. 8 Recently, efforts have been undertaken to arrive at a better qualification and standardization of SRP operations on Si. 9 Another development pursues higher depth resolutions to accurately analyze the ever decreasing dopant-structure sizes of electronic devices.…”
Section: Introductionmentioning
confidence: 99%